2022
DOI: 10.3389/fonc.2022.895834
|View full text |Cite
|
Sign up to set email alerts
|

A Model to Identify Candidates for Lymph Node Dissection Among Patients With High-Risk Endometrial Endometrioid Carcinoma According to Mayo Criteria

Abstract: BackgroundThe Mayo criteria are the most widely accepted algorithm for predicting the risk of lymph node metastasis in endometrial endometrioid carcinoma (EEC). However, the clinical value of these criteria in high-risk patients is limited and inconclusive.MethodsA total of 240 patients with EEC meeting the Mayo high-risk criteria between January 1, 2015, and December 31, 2018 were included in our study. We retrospectively collected the laboratory reports, basic clinical information, clinicopathological and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…Regarding laboratory parameters, in our cases we observed a correlation between a CA 125 value > 35 U/mL and lymph node positivity, with an odds ratio of 7.74 (95% CI 1.86-32.2). This aligns with findings from Lu et al's study, reporting a similar association between CA 125 > 35 U/mL and lymph node metastasis, with an odds ratio of 6.865 (95% CI, 2.481-20.840) [33]. Apart from CA 125, another laboratory parameter correlating with our observed outcomes is the preoperative platelet count.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding laboratory parameters, in our cases we observed a correlation between a CA 125 value > 35 U/mL and lymph node positivity, with an odds ratio of 7.74 (95% CI 1.86-32.2). This aligns with findings from Lu et al's study, reporting a similar association between CA 125 > 35 U/mL and lymph node metastasis, with an odds ratio of 6.865 (95% CI, 2.481-20.840) [33]. Apart from CA 125, another laboratory parameter correlating with our observed outcomes is the preoperative platelet count.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, it is not included in the standard diagnostic work-up of EC, due to its inability to offer differential diagnostic information. However, numerous studies have indicated that a preoperative CA 125 level > 35 IU/mL represents an independent risk factor for nodal positivity [28][29][30][31][32][33][34]. Additionally, growing evidence suggests that systemic inflammatory responders, such as the neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, C-reactive protein, platelets, and fibrinogen, may play a crucial role in the development and progression of solid tumors.…”
Section: Introductionmentioning
confidence: 99%